Synthesis and characterization of thiol-capped FePt nanomagnetic porous particles - Gao, X; Tam, K; Yu, K; Tsang, S (2005)
The synthesis and characterization of a thiol-capped FeOt magnetic alloy encapsulated within a thin porous silica overlayer with controlled dimensions using (3-mercaptopropyl)-trimethoxysilane (MPTS) as a precursor, is discussed. Elemental mapping of isolated nanoparticles by energy dispersive X-ray (EDX) analysis was carried out, in which isolated particles were randomly selected from the sample. A simple experiment of mixing the thiol-treated FePt nanoparticles with hydrazine indicated their total inactivity towards hydrogen formation whereas a small degree of exposed metal surface can liberate hydrogen from this reagent at room temperature. This simple synthetic methodology incorporates both magnetic and chemical storage functions into a single nanometer porous particle, which could extend the application of strong but reactive magnetic alloys such as FePt, FePd, FeCoPt, and FePt/Ag for magnetic separation.